State of sustainability assessments of metal additive manufacturing: literature review and triple-bottom-line perspectives - Nur Safirah Bahuriddin; Muhamad Zameri Mat Saman; Nurhasyimah Mohamad-Ali; Nor Hasrul Akhmal Ngadiman; Muhd Ikmal Isyraf Mohd Maulana (Environmental Science and Pollution Research, 2025)
With growing global energy and climate concerns, metal additive manufacturing (AM) has emerged as an innovative solution, offering various advantages, particularly in minimizing environmental effects. However, the sustainability assessment of metal AM, in particular, environmental, economic, and social impacts under the triple-bottom-line (TBL) has not been adequately communicated to guarantee high-quality outcomes. This study reviews emerging sustainability assessment of metal AM, focusing on papers addressing multiple sustainability dimensions. Several parameters are critically analyzed, including sustainability dimensions, sustainability indicators, circular economy domain, life cycle stages, metal AM technology, and others. The findings indicate that life cycle assessment and life cycle costing are the most commonly used methods; however, both are applied independently, with no effort to integrate them into a single sustainability score. Besides, the environmental dimension is the primary consideration, while the economic and social dimension lacks sufficient exploration. From the perspective of life cycle stages, the AM stage is the primary focus within the system boundary, whereas the design, use and end-of-life stages are underrepresented. Resource efficiency is covered within the circular economy domain, while recycling, a fundamental aspect of metal AM with considerable potential, remains overlooked. This study serves as a valuable reference to enhance the inclusivity of sustainability assessments of metal AM, focusing on integrating TBL, life cycle stages, indicator reliability and recycling aspects.

A model for end-of-life recovery in the automotive sector in Malaysia - Nurhasyimah Mohamad-Ali; Muhamad Zameri Mat Saman; Raja Ariffin Raja Ghazilla (Sustainable Production and Consumption, 2024)

Sustainability evaluation of alternative part configurations in product design: weighted decision matrix and artificial neural network approach - Mohd Fahrul Hassan; Muhamad Zameri Mat Saman; Safian Sharif; Badrul Omar (Clean Technologies and Environmental Policy, 2016)